1993
DOI: 10.1288/00005537-199310000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of sudden deafness with and without vertigo

Abstract: The outcome of unilateral sudden deafness with and without vertigo was evaluated according to the severity of the initial hearing loss, the shape of the audiogram, and other variables. The subjects for this investigation were 1313 patients who had presented to the authors' university hospital from 1972 to 1990 within 2 weeks of the onset of hearing loss. Thirty percent of the patients had accompanying vertigo. Vertigo occurred frequently in patients with severe hearing loss in the high-tone frequencies. Hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
1
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 13 publications
9
70
1
6
Order By: Relevance
“…Four types of inner ear ischemia are proposed. Recent work of Nakashima and Yanagita [20] showed that in 30% of the cases accompanying vertigo was found in sudden deafness. In these cases of sudden deafness and vertigo the Tange hearing loss was most frequently found in the high-tone frequencies.…”
Section: Discussionmentioning
confidence: 98%
“…Four types of inner ear ischemia are proposed. Recent work of Nakashima and Yanagita [20] showed that in 30% of the cases accompanying vertigo was found in sudden deafness. In these cases of sudden deafness and vertigo the Tange hearing loss was most frequently found in the high-tone frequencies.…”
Section: Discussionmentioning
confidence: 98%
“…[4,11,18,25,26] The most widely accepted concept is that the treatment outcome will be better when treatment is initiated within the first 7-10 days. [4,18] In a study including 326 patients, Huy and Sauvaget [16] found no difference in treatment outcome between day 1 and day 6 when the treatment was initiated within the first week.…”
Section: Discussionmentioning
confidence: 99%
“…Mūsų tyrimas parodė, kad kuo pacientas vyresnis, tuo tikėtinas klausos pagerėjimas mažesnis. ŪINKP tarp vaikų yra retas, pacientai, jaunesni nei 14 metų, sudaro tik 3,5% sergančiųjų ŪINKP [45]. Reliatyviai maža gydytų vaikų grupė, nenuoseklūs klausos tyrimų rezultatai, išsiskiriančios nuomonės dėl gydymo medikamentais tikslingumo neleidžia pateikti statistiškai patikimų išvadų [1, 30,45,46].…”
Section: Diskusijaunclassified
“…Pacientams, sergantiems ŪINKP, buvo tiriami ir rasti pakitę šie parametrai: sumažėjęs CD3+, CD4+, CD8+ limfocitų skaičius, padidėjęs lygiųjų raumenų antikūnų kiekis, rasta antiendotelio ląstelių antikūnų, kryžminių reakcijų antikūnų (27,45,50,80 kd), nerasta antikūnų prieš skydliaukę ir branduolius [4, 16,53,54]. Kiti mokslininkai pacientams, sergantiems ŪINKP, rado antikūnų prieš lygiųjų raumenų struktūras ir autoantikūnų,…”
Section: Diskusijaunclassified